1990
DOI: 10.1021/bi00488a017
|View full text |Cite
|
Sign up to set email alerts
|

65-Kilodalton protein phosphorylated by interleukin 2 stimulation bears two putative actin-binding sites and two calcium-binding sites

Abstract: We have previously characterized a 65-kilodalton protein (p65) as an interleukin 2 stimulated phosphoprotein in human T cells and showed that three endopeptide sequences of p65 are present in the sequence of l-plastin [Zu et al. (1990) Biochemistry 29, 1055-1062]. In this paper, we present the complete primary structure of p65 based on the cDNA isolated from a human T lymphocyte (KUT-2) cDNA library. Analysis of p65 sequences and the amino acid composition of cleaved p65 N-terminal peptide indicated that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Initial experiments revealed that L-plastin was phosphorylated at Ser 5 in IL-2-cultured human T lymphocytes (Supplemental Fig. 1A), which is consistent with reports that IL-2 induces L-plastin phosphorylation in T lymphocytes (24). Culturing the cells overnight in the absence of IL-2 or serum-starving the cells for 2 h in RPMI 1640 containing 0.5% BSA was sufficient to reduce the high basal levels of phosphorylation of L-plastin and ERK (Supplemental Fig.…”
Section: Resultssupporting
confidence: 90%
“…Initial experiments revealed that L-plastin was phosphorylated at Ser 5 in IL-2-cultured human T lymphocytes (Supplemental Fig. 1A), which is consistent with reports that IL-2 induces L-plastin phosphorylation in T lymphocytes (24). Culturing the cells overnight in the absence of IL-2 or serum-starving the cells for 2 h in RPMI 1640 containing 0.5% BSA was sufficient to reduce the high basal levels of phosphorylation of L-plastin and ERK (Supplemental Fig.…”
Section: Resultssupporting
confidence: 90%
“…The leukocyte (L)-plastin (LPL, also called plastin 2) isoform is exclusively expressed in mammalian leukocytes and is the only plastin isoform present in leukocytes. A serine site close to the N-terminus is phosphorylated by various immunological stimuli such as IL-2 or TCR ligands in T cells (24, 25). LPL has been shown to have a role in function of both neutrophils and T cells.…”
Section: Introductionmentioning
confidence: 99%
“…These two human cell type-specific isoforms, L-and T-plastin (80% amino acid identity), are expressed in hematopoietic cells and in cells derived from solid tissue, respectively [9] . In 1990, it was observed that an amino-terminal sequence containing a potential calcium binding domain was missing in the sequences reported earlier [10,11] . A third human plastin isoform, called I-plastin, was discovered as a polypeptide that is specifically expressed in the small intestine, colon and kidney, and is 86% identical to the chicken fimbrin (plastin) isoform [12,13] .…”
Section: Discoverymentioning
confidence: 97%